Advanced Glasses, Composites and Ceramics for High Growth Industries - Boccaccini, Aldo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Advanced Glasses, Composites and Ceramics for High-Growth Industries (CoACH) was a European Training Network (ETN) project (http://www.coach-etn.eu/) funded by the Horizon 2020 program. CoACH involved multiple actors in the innovation ecosystem for advanced materials, composed of five universities and ten enterprises in seven different European countries. The project studied the next generation of materials that could bring innovation in the healthcare, construction, and energy sectors, among others, from new bioactive glasses for bone implants to eco-friendly cements and new environmentally friendly thermoelectrics for energy conversion. The novel materials developed in the CoACH project pave the way for innovative products, improved cost competitiveness, and positive environmental impact. The present Special Issue contains 14 papers resulting from the CoACH project, showcasing the breadth of materials and processes developed during the project.